MANFAAT EKONOMI PEMBANGUNAN RUAS JALAN SIMPANG LAMIE – KUALA TUHA DITINJAU DARI ASPEK PRODUCER SURPLUS - Eddy Priatno; Sugiarto Sugiarto; Muhammad Isya (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2020)
The policy of Nagan Raya District Government to develop the Lamie - Kuala Tuha provincial road section aims to shorten travel time, reduce high mobility, facilitate travel, and support the movement of the plantation and agricultural sectors. This study aims to determine the magnitude of the benefits obtained from the producer surplus aspect in the plantation sector, agricultural sector and livestock sector and to evaluate economic feasibility based on Benefit Cost Ratio (BCR), Net Present Value (NPV), and Internal Rate of Return (IRR) . This research was conducted by collecting data related to the budget, wages, the Nagan Raya Regency Spatial Planning Book, the area of land and the production of the agricultural sector, the area of land and production of the plantation sector, and the amount and price of cattle. Data is processed by producer surplus method in the transportation economy, namely evaluating economic feasibility with BCR, NPV, IRR indicators. The results of this study indicate that the construction of the Lamie - Kuala Tuha Road in the 24th (twenty four) year or the 20th (twenty) year since the road was opened has met economic feasibility standards at a discount rate of 10, 12 and 15 percent with a value BCR 1.85, 1.54 and 1.15, NPV value of Rp. 64,828,481,000, Rp. 35,422,332,000 and Rp. 8,322,171,000. The IRR value obtained in this study is at the discount rate of 16.44 percent.